2017
DOI: 10.3892/etm.2017.5131
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of emodin against diabetic nephropathy in rat models are mediated via PI3K/Akt/GSK‑3β and Bax/caspase‑3 signaling pathways

Abstract: Abstract. Emodin is the main active component of the Chinese medicine rhubarb, which has a variety of pharmacological effects and a high clinical value. Its anti-inflammatory and antitumor effects have been widely studied. The aim of the present study was to determine whether emodin has renoprotective effects, and to identify the potential underlying mechanisms in a rat model of diabetic nephropathy (DN). The changes in mean blood glucose levels, normalized kidney weight, urinary albumin excretion, serum creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Intriguingly, significant decreases in p-Akt were observed in the GSJD-treated groups, which were accompanied by decreased apoptosis. These data are in agreement with reports about the inhibitory effects of emodin 38 , berberine 39 and astragaloside IV 40,41 , the bioactive constituents purified from the six herbs of GSJD, on p-Akt. Thus, our study suggested that the regulation of the mitochondrial apoptotic pathway and Akt pathway was most likely the basis for GSJD improving renal function in DN (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Intriguingly, significant decreases in p-Akt were observed in the GSJD-treated groups, which were accompanied by decreased apoptosis. These data are in agreement with reports about the inhibitory effects of emodin 38 , berberine 39 and astragaloside IV 40,41 , the bioactive constituents purified from the six herbs of GSJD, on p-Akt. Thus, our study suggested that the regulation of the mitochondrial apoptotic pathway and Akt pathway was most likely the basis for GSJD improving renal function in DN (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Fortunately, some of the compounds purified from the six herbs of GSJD have been used to treat DN and gained satisfactory results. For instance, astragaloside IV 26,[40][41][42][43][44][45][46] , berberine 39,[47][48][49][50][51] , emodin 38,52 and rhein 53,54 could ameliorate DN by modulating multiple signalling pathways. Therefore, further investigation of the active compounds in GSJD is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PI3K/Akt signal can also indirectly regulate mouse double microsomal 2 (MDM2), inhibiting p53, enhancing the activity of CREB and the function of Bcl2 [ 36 , 37 ]. Moreover, activation of Akt can suppress caspase-3 and inhibit GSK-3β activity, resulting in anti-apoptotic effect [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, through inhibiting mitochondrial complex I activity, emodin increases cellular ROS and Ca 2+ influx to activate AMPK, causing GLUT4 translocation and glucose uptake [ 55 ]. Emodin significantly improved the blood glucose of diabetic rats by activating the PI3K/Akt/GSK-3β signaling pathway [ 56 ]. Isolated chrysophanol from rhubarb rhizome increased tyrosine phosphorylation of the insulin receptor (IR) and accelerated GLUT4 mRNA expression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%